INVESTIGATION OF SOLAR THERMAL CHEMICAL PROCESSES OF STRUCTURE FORMATION OF ASH-CEMENT BINDERS USING SOLAR ENERGY - ALINAZAROV ALISHER KHAIDARALIEVICH; ULUKHANOV IBROHIM TUKHTAKHUZHAYEVICH; UBAYDULLAYEV SOLIJON QODIROVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
The article discusses the structure-forming factors and their influence on the technical and strength properties of a highly filled cast ash-cement mixture. A mathematical model of solar thermal chemical processes of structure formation of ash-cement binders using solar energy is proposed.